Finding a place in the SUN: telomere maintenance in a diverse nuclear landscape. (June 2016) - Ebrahimi, Hani; Cooper, Julia Promisel
Abstract : Telomeres function in the context of a complex nuclear milieu in which telomeres tend to occupy distinct subnuclear regions. Indeed, regulation of the subnuclear positioning of telomeres is conserved from yeast to human, raising the age-old question: to what extent is location important for function? In mitotically dividing cells, the positioning of telomeres affects their epigenetic state and influences telomere processing and synthesis. In meiotic cells, telomere location is important for homologue pairing, centromere assembly and spindle formation. Here we focus on recent insights into the functions of telomere positioning in maintaining genome integrity.